2017
DOI: 10.1186/s12974-016-0776-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-related macular degeneration associated polymorphism rs10490924 in ARMS2 results in deficiency of a complement activator

Abstract: BackgroundAge-related macular degeneration (AMD) is the leading cause of blindness in developed countries. The polymorphism rs10490924 in the ARMS2 gene is highly associated with AMD and linked to an indel mutation (del443ins54), the latter inducing mRNA instability. At present, the function of the ARMS2 protein, the exact cellular sources in the retina and the biological consequences of the rs10490924 polymorphism are unclear.MethodsRecombinant ARMS2 was expressed in Pichia pastoris, and protein functions wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 35 publications
0
62
0
9
Order By: Relevance
“…The authors show that ARMS2 binds to cell debris, where it promotes C3b generation and opsonization for phagocytosis by MPs. 10q26 risk-allele carriers would therefore lack necessary opsonization, promoting debris accumulation and AMD (Micklisch et al, 2017).…”
Section: Q26mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors show that ARMS2 binds to cell debris, where it promotes C3b generation and opsonization for phagocytosis by MPs. 10q26 risk-allele carriers would therefore lack necessary opsonization, promoting debris accumulation and AMD (Micklisch et al, 2017).…”
Section: Q26mentioning
confidence: 99%
“…pathogenic subretinal inflammation (Calippe et al, 2017;Levy et al, 2015a;Levy et al, 2015b;Liao et al, 2013;Micklisch et al, 2017). Importantly, the affected genes are all expressed in MPs and the consequences of the disease-associated variants directly affect MP function.…”
Section: General Considerations On Genetic Risk and Mononuclear Phagomentioning
confidence: 99%
“…One study found that ARMS2 was expressed in human monocytes and microglia cells and facilitated removal of cellular debris by local complement activation; the A69S variant resulted in ARMS2 deficiency, possibly impairing the removal of cellular debris at Bruch's membrane, leading to the development of drusen. 52 On the other hand, another study reported that ARMS2 mRNA and protein are expressed at extremely low levels in eye tissues, and presented support for HTRA1 as the risk factor for AMD. 53 We found that the OCT algorithm yielded drusen measurements that were highly associated with the manual CARMS grading.…”
Section: Discussionmentioning
confidence: 98%
“…Dieser Wirkung liegt eine direkte Hemmung des alternativen Komplementwegs zugrunde [29]. Eine Fehlregulation des alternativen Komplementwegs wiederum kann als Mitursache für die gestörte Mikroglia-/Makrophagenhomöostase in der Netzhaut von AMD-Patienten betrachtet werden [34]. Der in der vorliegenden Studie beobachtete antiangiogene, leckagereduzierende Effekt durch Polysialinsäure könnte einerseits durch die Verminderung des CNV-begünstigenden zellulären inflammatorischen Prozesses entstehen und andererseits durch eine Verminderung des komplementvermittelten Schadens am RPE/Aderhautkomplex erklärt werden [35].…”
Section: Diskussion Und Schlussfolgerungunclassified